SAT0198 PERIPHERAL NERVOUS SYSTEM INVOLVEMENT IN PRIMARY SJOGREN'S SYNDROME – UNCOMMON OR UNDERESTIMATED PROBLEM?. (June 2019) - Jaskolska, Marta; Chylinska, Magdalena; Masiak, Anna; Czuszynska, Zenobia; Galecka, Katarzyna; Sieminski, Mariusz; Smoleńska, Żaneta; Ziętkiewicz, Marcin; Zdrojewski, Zbigniew
Abstract : Background: Systemic manifestations are common in primary Sjögren's syndrome (pSS) and play a major role in the prognosis. Neurological complications may affect both the peripheral (PNS) and central nervous system (CNS). The incidence varies from several to several dozen percent. The course of the disease and the severity of the symptoms may be mild and self-limiting or progressive, leading to permanent neurological deficits. It is worth remembering that the symptoms of nervous system involvement may precede the onset of symptoms of dryness, and diagnosis of pSS may be delayed after a certain duration of neurological symptoms. Objectives: The aim of the study was to determine the prevalence of PNS involvement among symptomatic and asymptomatic patients with the diagnosis of pSS in our University Clinical Centre. Methods: We studied a consecutive group of fifty unselected patients aged from 33 to 74 years (mean 55.8 years). All patients fulfilled the criteria for the diagnosis of pSS. Additional connective tissue diseases and diabetes were the exclusion criteria. Disease activity was evaluated according to the EULAR Sjögren's syndrome disease activity index (ESSDAI). All patients underwent clinical neurological examination and nerve conduction studies (NCS) of nine peripheral nerves. For the classification of polyneuropathies the ESTEEM (European Standardized Telematic tool to Evaluate Electrodiagnostic Methods) guidelines were used. Clinical examination and nerve conduction study were performed and evaluated by one certified neurologist. Results: Of our 50 patients, 48 were female with a mean (±SD) age 53.6±10.5 years and mean disease duration 7.9±5.3 years. Two were male with mean age 43.7±25.8 years and mean disease duration 5.7±0.6 years. The mean age at diagnosis was 50.4±14 years. 23 (46%) patients fulfilled the criteria for the diagnosis of neuropathy. The most common PNS manifestation was sensorimotor neuropathy 11/23 (47%), mononeuropathy was present in 6/23 (26%) patients, pure axonal sensory neuropathy was present in 1/23 (4.3%) patient, axonal motor neuropathy in 1/23 (4.3%), SFN in 1/23 (4.3%) and cranial nerve involvement was present in 4/23 (17.4%) (one of the patients had both cranial and sensorimotor neuropathy). Neurological symptoms preceded the diagnosis of pSS in 8 (35%) of 23 PNS+ patients. The frequency of following symptoms and extraglandular manifestations was significantly higher in PNS+ compared to PNS- patients: salivary gland enlargement (74% vs 44% p<0, 05), respiratory tract involvement (65% vs 37% p<0, 05) and lymphadenopathy (61% vs 19% p<0, 05). The mean ESSDAI in patients with and without neurological involvement was 7±6, 82 and 4, 7±4, 58 respectively (p=0.245). In this subgroup the use of cyclophosphamide, due to extraglandular manifestations, was increased (p<0, 05). Conclusion: We found that PNS involvement is a common extraglandular manifestation of pSS (46% in our group). Sensorimotor neuropathies were most frequent. Involvement of the PNS seems frequent but remains underestimated. NCS is a non-invasive test which might be useful at diagnosis and follow-up. Guidelines for the diagnosis and treatment of peripheral neuropathies in patients with pSS are needed. Disclosure of Interests: None declared